PRELIMINARY ECOLOGOCAL STUDY OF Rhizobium : SELECTION OF ANTIBIOTIC RESISTANT MUTANTS OF Rhizobium PMA295 NODULATING Sesbania sesban - Nurhayati D. Purwantari (Indonesian Journal of Agricultural Science, 2000)
This study was designed to provide strain for studying the ecology of Rhizobium when it was used to inoculate seed sown in the soil or in the field. Naturally occurring antibiotic resistant mutant strains of Rhizobium PMA295 nodulating Sesbania sesban were selected by antibiotic selection method. The isolates should be as effective  in nitrogen fixation as the parental  wild-type strain. Authentication of mutant isolates showed that these rifampicin mutant isolates could nodulate test plant and most nodules formed by the rifampicin 50 ppm and streptomycin 500 ppm mutant isolates were red in colour. These twenty isolates can be regarded as rhizobia. The most effective mutant, isolates PMA295 selected on rifampicin 50 ppm was also resistant to rifampicin 60, 70, 80, and 90 ppm. The effectiveness of most mutant strains was not significantly different from their parent strains. The rifampicin 50 ppm mutant strain of Rhizobium PMA295 could be used as inoculant for ecological study.